2015
DOI: 10.1002/erv.2425
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Adolescent Patients with Anorexia Nervosa and Unipolar Affective Disorders

Abstract: Studies have shown impairments in cognitive function among adult patients with anorexia nervosa (AN) and affective disorders (AD). The association between cognitive dysfunctions, AN and AD as well as the specificity for these psychiatric diagnoses remains unclear. Therefore, we examined cognitive flexibility and processing speed in 47 female adolescent patients with AN, 21 female adolescent patients with unipolar affective disorders and 48 female healthy adolescents. All participants completed a neuropsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(88 reference statements)
1
2
0
1
Order By: Relevance
“…Nonetheless, in Doğan ( 2001)'s study, it was found that the aggression levels of women were higher than that of men, and this fact shows that it differs from the current research results. Some studies concluded that the cognitive flexibility dimension does not differ depending on gender (Martin and Rubin, 1995;Zong et al, 2010;Sarrar et al, 2013;Plukaard et al, 2015). Both the results of the literature and the current study findings show that the cognitive flexibility of athlete students is similar.…”
Section: Discussion and Conclusion Recommendationssupporting
confidence: 73%
“…Nonetheless, in Doğan ( 2001)'s study, it was found that the aggression levels of women were higher than that of men, and this fact shows that it differs from the current research results. Some studies concluded that the cognitive flexibility dimension does not differ depending on gender (Martin and Rubin, 1995;Zong et al, 2010;Sarrar et al, 2013;Plukaard et al, 2015). Both the results of the literature and the current study findings show that the cognitive flexibility of athlete students is similar.…”
Section: Discussion and Conclusion Recommendationssupporting
confidence: 73%
“…These participants, however, displayed normal general intelligence and normal set shifting ability. Subtle differences in neurocognitive functioning may thus exist in adolescents with AN, [ 29 31 ] or even in subgroups, despite their function being similar to controls on most neurocognitive measures [ 22 , 23 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…В работах, посвященных более длительным периодам голодания у людей, результаты оценки когнитивных функций сопоставимы с нашими результатами. Моделью многолетнего резкого ограничения калорийности рациона могут являться пациенты с неврогенной анорексией: большинство таких больных демонстрировали худшее выполнение когнитивных тестов по сравнению с контрольной группой пациентов с униполярными аффективными расстройствами [21]. Также при наблюдении за здоровыми лицами было выявлено, что снижение массы тела ассоциировалось с более высоким риском развития деменции, чем поддержание стабильной массы тела [22].…”
Section: обсуждение основного результата исследованияunclassified